'Wearing down of the self': Embodiment, writing and disruptions of identity in transformational festival fieldwork. Issue 1 (August 2017) - Ruane, Deirdre
Immersive ethnographic research can be profoundly destabilising for researchers' sense of identity, and the attempt to inhabit and reconcile dual identities as researcher and participant can take a severe emotional toll. Prior to the reflexive turn in qualitative sociology, this identity work remained largely unacknowledged. Feminist critiques of positivist social science, along with personal accounts portraying the messy, chaotic aspects of research, have helped to create a new climate in which researchers can openly examine their identity conflicts and even recognise them as an integral part of their research. However, advice on navigating these situations remains somewhat limited. This article is a reflexive account of issues encountered while researching the practice of psychedelic support – the provision of emergency care to people undergoing drug-related crises – within the transformational festival scene in the United Kingdom, the United States and Portugal. Transformational festival settings are engineered to disrupt everyday experiences of identity and selfhood and induce emotional vulnerability. Thus, they throw issues of researcher identity and its management into sharp relief. Physically and emotionally intense fieldwork settings can bring about non-ordinary mental states in the researcher which can put habitual working practices and capacities out of reach. This effect contributed to a painful disjunction between my researcher and participant identities, which centred on the struggle to create linear, written narratives of largely embodied and non-verbal experiences. However, I found that the effect was somewhat mitigated by developing fluid, non-linear, multisensory working practices and documentation methods which were more appropriate to the research setting and the mental states it induced. I conclude that ethnographers in intense or extreme field settings can benefit greatly from methods and tools which work even when we are out of our everyday minds.